Breaching of a perennial snow dam below Lake Hyoga Ike in the Langhovde region of the Sôya Coast, East Antarctica: Probable effect of disturbance events on the distribution and colonization of flora within/around the lake - Sakae Kudoh; Yukiko Tanabe; Takeshi Inoue; Satoshi Imura; Hiroshi Kanda (National Institute of Polar Research, 2009)
The distribution and colonization of flora in Antarctica may be limited by disturbance events, including flooding. Recently, we observed a large hole in the perennial snow dam below Lake Hyoga Ike (temporary name), located in the Langhovde region on the Sôya Coast in East Antarctica. This phenomenon was also reported by a previous Japanese Antarctic Research Expedition, almost 25 years earlier. The earlier breakage was subsequently closed and the lake was refilled. At present, the surface area of the lake has decreased significantly due to the loss of water. Many of the neighboring valleys and lakes in the southern part of the Langhovde area contain well-developed colonies of algae, mosses, and lichens. By contrast, both Lake Hyoga Ike and the river below the snow dam contain very little flora. Such a contrast in the distribution and colonization of flora suggests that the repeated occurrence of physical disturbances, induced by breaching of the dam, may be a critical factor limiting flora in this ice-free region of Antarctica. We recommend long term observation of the fate of the ice cave and changes in the lake level for the purpose of evaluating climatic change and ecology. The observations also contribute to the maintenance of safety in the field works in this area.